Pengaruh Pertumbuhan Ekonomi terhadap Tingkat Pengangguran: Analisis Hukum Okun - Darman Darman (Bina Nusantara University, 2013)
The concept of a negative relationship between economic growth (Gross Domestic Product) and unemployment rate is known as Okun's law (Okun's Law) or the Okun coefficient. The application of Okun's law in Indonesia uses time series data from 1999 to 2013. The method used is the difference version of Okun's law to gain Okun coefficient and Ordinary Least Square (OLS) analysis to obtain the regression coefficients. In a macro-economic framework, Okun's law states that if the GDP grows at 2.5% above the trend, which has been achieved in a given year, the unemployment rate will fall by 1 %. From various studies conducted by several researchers can be seen that the Okun coefficient in each different country. In Indonesia, the scientific literature that specifically raised the Okun's law does not available, so the study aims to look at how the application of Okun's law in Indonesia The results showed that Okun's law applies in Indonesia, where the Okun coefficient is negative. The unemployment rate tends to increase in line with GDP growth reached.